Application of the Strongin-Sergeyev global optimization method in the compliance minimization of latticed shells - Czarnecki, Sławomir (Computer Assisted Methods in Engineering and Science, 2017)
The aim of the present paper is to revisit some known truss optimization problems by applying the genuine Strongin and Sergeyev's algorithm of the global search [8]. By employing the space-filling Hilbert-Peanotype curves, the wide class of non-convex and multidimensional constrained global optimization problems is reduced to one-dimensional ones. Then, the global minimum of the objective function in one-dimensional problem can be effectively found by means of Multivariate Index Method (MIM) that can be treated as a special version of one-dimensional Global Search Algorithm (GSA) over the set of open intervals adopted to constrained problems.